Effects of backpack weight on the performance of basic short-term/working memory tasks during flat-surface standing. Issue 4 (3rd April 2019) - Son, Minseok; Hyun, Soomin; Beck, Donghyun; Jung, Jaemoon; Park, Woojin
Abstract: This study empirically investigated the effects of backpack weight on the performance of three basic short-term/working memory (STM/WM) tasks during flat-surface standing. Four levels of backpack weight were considered: 0, 15, 25 and 40% of the body weight. The three STM/WM tasks were the Corsi block, digit span and 3-back tasks, corresponding to the visuo-spatial sketchpad, phonological loop and central executive of WM, respectively. Thirty participants conducted the STM/WM tasks while standing with loaded backpack. Major study findings were that (1) increased backpack weight adversely affected the scores of all three STM/WM tasks; and, (2) the adverse effect of backpack weight was less pronounced for the phonological loop STM task than the other STM/WM tasks. The study findings may help understand and predict the impacts of body-worn equipment weight on the worker's mental task performance for various work activities requiring simultaneous performance of mental and physical tasks. Practitioner summary: The current study empirically examined the effects of backpack weight on the performance of three basic STM/WM tasks. The study findings entail that reduces the weight of body-worn equipment can positively impact the worker's mental task performance in addition to reducing the worker's bodily stresses. Abbreviations : ACC: anterior cingulate cortex; AP: anterior-posterior; BW: body weight; CoP: centre of pressure; C-S: central executive working memory task and standing; DLPFC: dorsolateral prefrontal cortex; HIP: human information processing; ML: medio-lateral; PMC: premotor cortex; P-S: phonological loop short-term memory task and standing; SMA: supplementary motor area; STM: short-term memory; VLPFC: ventrolateral prefrontal cortex; V-S: visuo-spatial short-term memory task and standing; WM: working memory